Development of a Problem-Based Monopoly Game Integrating Contextual Social Issue Challenges for Elementary Social Studies Learning - Debima Jejen Junior Robbyzess; Otib Satibi; Ika Lestari (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
The limited use of interactive and problem-oriented learning media in elementary social studies classrooms has contributed to low student engagement and weak problem-solving skills. Although game-based learning has gained increasing attention, studies integrating Monopoly game mechanics with Problem-Based Learning (PBL) in elementary social studies remain limited. Therefore, this study aimed to develop a PBL-integrated Monopoly learning media and examine its validity and practicality. This study employed a Research and Development (R&D) approach using a 4D model consisting of define, design, develop,  and dissemination stages. The subjects involved media experts, material experts, linguists, teachers, and fourth-grade elementary school students. Data were collected through validation questionnaires, teacher and student response questionnaires, cognitive tests, and observations of student activities. Data were analyzed using descriptive quantitative and qualitative techniques. The findings showed that the developed media achieved high validity scores, namely 92.0% from media experts, 91.6% from material experts, and 93.3% from language experts. Validators nevertheless suggested improvements related to instruction clarity, visual consistency, and optimization of PBL activities within the game. Practicality results also showed positive responses from students (93.2%) and teachers (93.5%), although some students initially experienced difficulties in understanding the collaborative problem-solving process. Therefore, the developed PBL-integrated Monopoly media can be categorized as valid and practical for elementary social studies learning, while further refinement and broader implementation are still needed to optimize its instructional effectiveness.